Exploring shape diversity and sexual dimorphism in two populations of Nigma conducens through geometric morphometrics - Safa M. El-masry; Tarek G. Ismail; Asmaa N. Mustafa (BMC Zoology)
Abstract Background Spiders are highly adaptable hunters found in nearly all terrestrial ecosystems and play an important role in biological control by preying on pest insects. Spiders’ body size and shape are vital for their survival, particularly in prey capture, and these morphological features are often utilized in cladistic analyses. This study employed geometric morphometrics to investigate prosoma shape and size variations between two populations of Nigma conducens spiders and between sexes within each population. Principal Component Analysis (PCA) explored shape variation, while Canonical Variate Analysis (CVA) compared shape differences between populations and sexes. Multivariate regression analysis was used to check for allometry. Results MANOVA results revealed significant shape variations in spider prosoma between the two populations and between sexes, though the degree of these differences was small. The considerable overlap in individual shapes between populations may indicate a response to microhabitat similarity. Additionally, sexual dimorphism was observed in the prosoma shape of N. conducens, likely due to sexual selection or adaptive divergence related to different microhabitats. Size differences between sexes were insignificant in either population, particularly in the first, suggesting that prosoma size does not contribute to reproductive success. Moreover, the non-allometric relationship indicated that shape variations between the populations were independent of size. Conclusion Overall, these findings highlight the complexity of morphological adaptations in N. conducens in response to ecological pressures and sexual selection.